The Organization Theories of the Industrial Democracy Experiments Meet Contemporary Organizational Realities - Klemsdal, Lars; Ravn, Johan E.; Amble, Nina; Finne, Håkon (Nordic Journal of Working Life Studies, 2017)
The Scandinavian industrial democracy experiments (IDEs) contained elements of organization theories, based particularly on sociotechnical systems theory (STS). In this paper, we provide an introduction to some main points of these theories and their aftermath, as a context for the six papers of the special issue on the relevance of the organization theories of the IDE for contempo- rary organizational realities.The six papers are also summarized and positioned in relation to the theoretical insights from the IDE.